2015
DOI: 10.1167/iovs.15-17022
|View full text |Cite
|
Sign up to set email alerts
|

The Negative Cone Mosaic: A New Manifestation of the Optical Stiles-Crawford Effect in Normal Eyes

Abstract: PURPOSE. The purpose of this study was to describe a previously unreported manifestation of the optical Stiles-Crawford effect (oSCE) in normal eyes. METHODS.In a cohort of 50 normal subjects, the directional reflectance of cones in the retinal periphery was explored by flood-illuminated adaptive optics (FIAO) and optical coherence tomography (OCT). RESULTS.In 32 eyes (64%), off-axis FIAO images of the retinal periphery (~15-208 from the fovea) showed variably sized patches of hyporeflective dots (called here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…However, Vohnsen [30] has previously shown that this can only have an impact when the angle of incidence on the retina is greater than 7 degrees corresponding to a pupil entrance displacement of 2.7 mm. In previous work [24], the reflectance of the cones in AO flood-illuminated images of the retinal periphery has been shown to be greatly influenced by large displacements of the entry pupil. It is well known that the cones have relatively narrow angular reflectance functions, returning much more of the incident light towards a point near the center of the pupil than towards points farther away from the center.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…However, Vohnsen [30] has previously shown that this can only have an impact when the angle of incidence on the retina is greater than 7 degrees corresponding to a pupil entrance displacement of 2.7 mm. In previous work [24], the reflectance of the cones in AO flood-illuminated images of the retinal periphery has been shown to be greatly influenced by large displacements of the entry pupil. It is well known that the cones have relatively narrow angular reflectance functions, returning much more of the incident light towards a point near the center of the pupil than towards points farther away from the center.…”
Section: Discussionmentioning
confidence: 94%
“…The reflectance studies have been performed with all AO imaging modalities, including AO-SLO [11][12][13]16], AO-OCT [14] and flood-illuminated AO cameras [9,17,24]. The most common explanation so far for the cone reflectance variability of the order of an hour is the disc renewal process [9], which is thought to be the cause of both change in the outer segment length, observable through interference produced with a long-coherence light source AO-SLO [12], and in the refractive index at the interface between the inner and the outer segment, observable also with a short-coherence light source AO-SLO-OCT [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AO is also useful to detect minute changes in vessel morphology (Paques et al 2015). Analysis of photoreceptor pointing on off-axis images are of interest in macular diseases, in which the visualization of the cone mosaic can be dramatically modified by multiangle observation (Miloudi et al 2015). In uveitis patients, we observed that paravascular inflammation (perivenous sheathing) may be more easily detected by AO than by other means (Errera et al 2014), providing us with a tool for mapping the extent of perivenous sheathing in cases of uveitis.…”
Section: Adaptive Optics For Retinal Imagingmentioning
confidence: 99%